2015
DOI: 10.1371/journal.pone.0129172
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Phosphatidylcholine-Coated Gold Nanoparticles in Orthotopic Pancreatic Adenocarcinoma using Hyperspectral Imaging

Abstract: Nanoparticle uptake and distribution to solid tumors are limited by reticuloendothelial system systemic filtering and transport limitations induced by irregular intra-tumoral vascularization. Although vascular enhanced permeability and retention can aid targeting, high interstitial fluid pressure and dense extracellular matrix may hinder local penetration. Extravascular diffusivity depends upon nanoparticle size, surface modifications, and tissue vascularization. Gold nanoparticles functionalized with biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 53 publications
4
40
0
Order By: Relevance
“…Characterization via zeta potential analysis showed that three-layer nanoparticles displayed a relatively neutral surface charge of -6 mV, while two-layer nanoparticles were more anionic at -21 mV (Table 2). The measurements were consistent with previous work [36][37][38]. Dynamic light scattering (DLS) provided further information regarding size based upon Brownian motion when in solution [56].…”
Section: Nanoparticle Characterizationsupporting
confidence: 89%
See 2 more Smart Citations
“…Characterization via zeta potential analysis showed that three-layer nanoparticles displayed a relatively neutral surface charge of -6 mV, while two-layer nanoparticles were more anionic at -21 mV (Table 2). The measurements were consistent with previous work [36][37][38]. Dynamic light scattering (DLS) provided further information regarding size based upon Brownian motion when in solution [56].…”
Section: Nanoparticle Characterizationsupporting
confidence: 89%
“…This assumes first-order kinetics, for which the extravasation is mainly concentration dependent. The decay α is measured from previous in vivo experiments, for which the nanoparticle concentration is estimated to have a half-life of 12 h [37]. Although nanoparticle diffusivity can be dependent on charge [53] in addition to size, for this study we calibrate the diffusivity to the combination of these properties as measured from the in vitro data [36].…”
Section: Transport Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were also obtained in S2-VP10 orthotopic xenograft tumor and showed the predictive value of MCTS. 104 The same statement holds for growth inhibition effects measured in MCTS and in vivo tumors subjected to NPs' treatment. The similarity between the evolution of spheroid volume and tumor growth after treatment constitutes a great advantage with respect to 2D cell models.…”
mentioning
confidence: 86%
“…1,[8][9][10][11] Due to their physical properties and potencies, nanoparticles have proven to be highly versatile and can be widely used in numerous applications. 6,[12][13][14] Their size and shape properties are compatible with various biomedical applications that require interaction with smallmolecule antibiotics. The size of these nanomaterials provides a large surface-areato-volume ratio, which enables the binding of a large number of high affinity ligands, allowing for nanoparticle multivalency in fighting bacteria.…”
Section: Introductionmentioning
confidence: 99%